Explaining Green Skincare Purchase Intention: The Role of Attitudes and Usage Barriers - Ita Nurcholifah; Heny Hidayati; Muhammad Rafiuddin; Hesham Saleem Al Naggar (Universitas Pendidikan Nasional, 2026)
This study aims to explain the formation of green skincare purchase intention among Generation Z consumers in Indonesia by examining the roles of environmental values and perceived health benefits in shaping consumer attitudes, and the moderating effect of usage barriers on the attitude–intention relationship. This study adopted a quantitative approach and surveyed 263 Indonesian Generation Z consumers with prior experience using green skincare products. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results indicate that both environmental values and perceived health benefits significantly and positively influence consumer attitudes toward green skincare, with health benefits exerting a stronger effect. Consumer attitudes are strong determinants of purchase intention. Crucially, the structural model exhibits high explanatory and predictive power, explaining a substantial proportion of purchase intention (R² = 0.642) and demonstrating high predictive relevance (Q²_predict = 0.598). Moreover, usage barriers significantly and negatively moderate the relationship between attitude and purchase intention, weakening the translation of positive attitudes into buying intentions. This study contributes to the green consumption literature by integrating the Theory of Planned Behavior (TPB) and Innovation Resistance Theory (IRT) to demonstrate that usage barriers function as a boundary condition rather than a direct predictor, thereby offering a nuanced explanation of the attitude–intention gap in high-involvement green products. Therefore, the findings suggest that managers should prioritize the credible communication of health benefits while simultaneously reducing functional barriers to use. Policymakers are advised to strengthen standards and transparency for green skincare claims to support informed and confident consumer decision-making.